2023
DOI: 10.1007/s00429-023-02667-2
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of resting-state networks following repetitive transcranial alternating current stimulation of the dorsolateral prefrontal cortex

Abstract: Transcranial alternating current stimulation (tACS) offers a unique method to temporarily manipulate the activity of the stimulated brain region in a frequency-dependent manner. However, it is not clear if repetitive modulation of ongoing oscillatory activity with tACS over multiple days can induce changes in grey matter resting-state functional connectivity and white matter structural integrity. The current study addresses this question by applying multiple-session theta band stimulation on the left dorsolate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Here, it is worth highlighting that the precuneus, along with several other regions in the parietal cortex, forms a major node of the default mode network (DMN), a network associated with attentional mechanisms (Utevsky et al, 2014). Stimulation of left-DLPFC has been reported to modulate the activity in the parietal cortex possibly through network level modulation (van der Plas et al, 2021; Khan et al, 2023). Particularly the study by van der Plas et al reported an enhancement in memory performance and an increase in beta desynchronization in the parietal brain regions after left-DLPFC stimulation with TMS during the encoding of memories (van der Plas et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Here, it is worth highlighting that the precuneus, along with several other regions in the parietal cortex, forms a major node of the default mode network (DMN), a network associated with attentional mechanisms (Utevsky et al, 2014). Stimulation of left-DLPFC has been reported to modulate the activity in the parietal cortex possibly through network level modulation (van der Plas et al, 2021; Khan et al, 2023). Particularly the study by van der Plas et al reported an enhancement in memory performance and an increase in beta desynchronization in the parietal brain regions after left-DLPFC stimulation with TMS during the encoding of memories (van der Plas et al, 2021).…”
Section: Discussionmentioning
confidence: 99%